MARKETING ANALYSIS OF ADEMETHIONINE ІN THE PHARMACEUTICAL MARKET OF UKRAINE - Драчук, Віра; Заморський, Ігор; Щудрова, Тетяна; Копчук, Тамара; Горошко, Олександра; Дикал, Мар’яна (SWorldJournal, 2023)
The article presents the results of the marketing analysis of Аdemethionine presented on the pharmaceutical market of Ukraine. A review of literature sources on preclinical and clinical studies was conducted, the main areas of application of the drug were